Gabapentin-Induced Myokymia: A Case Report. Issue 2 (21st March 2021) - Brown, Alexander; Esechie, Aimalohi; Gogia, Bhanu; Shanina, Elena
Abstract : Background: Gabapentin is a commonly used medication for neuropathic pain and epilepsy that is prescribed by a wide range of medical specialties. Adverse effects including asterixis and myoclonus have been described in patients with chronic kidney disease, but myokymia has not been previously reported. Case Presentation: A 69-year-old man with a history of traumatic brain injury, peripheral neuropathy, amnesia, and posttraumatic stress disorder presented to the hospital after multiple falls attributed to acute onset muscle spasms. He reported taking a total daily dose of 9600 mg of gabapentin, as prescribed. Physical examination demonstrated stimulus-sensitive myoclonus, painful muscle spasms in all extremities, and myokymia in his bilateral calves. Diffuse action tremors, as well as tongue tremors, were also observed. Initial workup, including basic laboratory investigations, brain imaging, and electroencephalogram, was unrevealing. Gabapentin toxicity was suspected, and a gabapentin holiday was initiated with the improvement of myokymia by hospital day 3. The patient was found to have a high gabapentin level (25.8 μg/mL; reference range, 2.0–20.0 μg/mL) measured the morning after hospital presentation. After restarting on a lower dose of gabapentin with multimodal pain control, the patient continued to improve with diminution of his myoclonus, tremor, and gait instability. Conclusions: Myokymia is a newly described motor symptom associated with gabapentin toxicity. The mechanism of gabapentin-associated myokymia is currently unknown. A brief medication holiday resulted in the resolution of motor symptoms without significant withdrawal symptoms. Knowledge of this newly reported adverse manifestation can aid physicians in the diagnosis of gabapentin toxicity and prompt treatment, as gabapentin levels are not widely or immediately available.